The Village - Series One Episode 1-6 - Bird, Antonia; MacKinnon, Gillies; Odd, David; Simm, John; Peake, Maxine; Evans, Rupert; Stevenson, Juliet (Entertainment One, 2013)
"The Village" is an epic drama series for BBC One starring Maxine Peake and John Simm, charting the life and turbulent times of one English village across the whole of the 20th century, written by Bafta-winning writer Peter Moffat. "The Village" charts the life and turbulent times on one English village throughout the twentieth century with the life and memories of one man, Bert Middleton, providing the backbone to the story as he lives across the entire hundred years. From boyhood to extreme old age Bert witnesses births and deaths, love and betrayal and the great political events and social upheaval that shaped and made Britain and his village what it is today. [www.amazon.co.uk]
Keywords: DVD-Video